PENGARUH KOMUNIKASI, BUDAYA ORGANISASI DAN LINGKUNGAN KERJA FISIK TERHADAP KEPUASAN KERJA - Ni Koming Pramiti; Ni Nyoman Suryani; Gde Bayu Surya Parwita (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2019)
Job satisfaction is an evaluation that describes someone for feeling happy, or not happy, satisfied or dissatisfied at work. Therefore, to get employee job satisfaction, themanagement of the company must pay attention to factors that affect employee job satisfaction. This study aims to find out the communication, organizational culture, and physical work environment influencing employee job satisfaction. The analysis technique used is multiple linear regression test. The data used is primary data with a research instrument in the form of a questionnaire. The study population was all employees with a sample of 32 respondents. The results of this study indicate a positive influence of communication, organizational culture, and physical work environment on employee job satisfaction. Based on the results of the t test, the communication has a positive and significant effect on employee job satisfaction, the variable of organizational culture has a positive and significant effect on employee job satisfaction and the physical work environment has a positive and significant effect on employee job satisfaction. Based on the results of the F test, the communication variables, organizational culture and physical work environment have a positive and significant effect on employee job satisfaction.